Analisis Dan Perancangan Bangun Sistem Penjualan Obat Pada Apotek Karya Husada Perdagangan - Napitupulu, Kevin Ronaldo Martua; Hartanto, Bobby; Rusmewahni, Rusmewahni; Harahap, Hastuti Handayani (STIE Bina Karya, 2025)
This study aims to analyse and design a web-based drug sales information system for Apotek Karya Husada Perdagangan. The pharmacy still uses a manual system for recording transactions, managing inventory, and generation reports. The research applies the Waterfall method with a descriptive qualitative approach. Data were collected through interviews, observations, and literature study. The system was developed using PHP, a MySQL database, and the CodeIgniter framework. System testing was conducted using the Black Box method, and the results show that all features function properly without errors. The system supports transaction recording, inventory management, and the generation of daily, monthly, and annual sales reports. The implementation of this information system is expected to improve operational efficiency, reduce recording errors, and enhance service quality at Apotek Karya Husada.